2015
DOI: 10.1185/03007995.2015.1020365
|View full text |Cite
|
Sign up to set email alerts
|

Effects of desvenlafaxine on blood pressure in patients treated for major depressive disorder: a pooled analysis

Abstract: Short-term desvenlafaxine treatment was associated with small but statistically significant increases in SSBP and SDBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…In a pooled analysis of short-term studies on desvenlafaxine, there were significant increases in supine systolic BP and supine diastolic BP in the pooled desvenlafaxine 50- and 100-mg groups compared with those in the placebo group [ 14 ]. By contrast, long-term safety regarding BP change was documented in a double-blind, placebo-controlled, randomized withdrawal study with 50 mg/d of desvenlafaxine, where there was no significant BP change at the final evaluation when compared to the placebo [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a pooled analysis of short-term studies on desvenlafaxine, there were significant increases in supine systolic BP and supine diastolic BP in the pooled desvenlafaxine 50- and 100-mg groups compared with those in the placebo group [ 14 ]. By contrast, long-term safety regarding BP change was documented in a double-blind, placebo-controlled, randomized withdrawal study with 50 mg/d of desvenlafaxine, where there was no significant BP change at the final evaluation when compared to the placebo [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The side-effect profile of desvenlafaxine was found consistent with that of other SNRIs and the efficacy of desvenlafaxine has been demonstrated through short- and long-term clinical trials, but these included few Asian participants [ 11 - 13 ]. As an SNRI, desvenlafaxine may also result in blood pressure (BP) elevation [ 10 , 14 ]. However, this has not been confirmed in the Asian population, especially over a long-term period.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown a small but significant increase in blood pressure. 36,37 However, Speroff et al, 26 did not find a difference in adverse effects with placebo after 52 weeks of treatment.…”
Section: Pharmacological Approachesmentioning
confidence: 94%
“…Los efectos secundarios, como náuseas, insomnio y sequedad bucal, fueron observados solamente en la primera semana de tratamiento. Algunos estudios han mostrado un pequeño pero significativo aumento en la presión arterial (26,27) . Sin embargo, Speroff y col (16) no encuentran diferencia con el placebo en los efectos adversos, luego de 52 semanas de tratamiento.…”
Section: Introductionunclassified